Effluent from Winery Waste Biorefinery: A Strategic Input for Biomass Generation with Different Objectives to Add Value in Arid Regions - Rizzo, Pedro Federico; Aguado, German Dario; Funes Pinter, Mariano Ivan; Martinez, Laura Elizabeth; Ferrari, Florencia; De Biazi, Federico Sebastian; Martín, Pablo; Flores, Gustavo; Sánchez, Antoni; Uliarte, Ernesto Martin (MDPI, 2025)
Agro-industrial activities generate significant amounts of organic waste and a variety of effluents thus posing environmental challenges. Viticulture in Argentina, which covered 204,847 ha in 2023, faces water scarcity as a limiting factor conditioning its production. This industry produces large volumes of grape marc, sediments, and stalks, which can be valorised into products like alcohol, tartaric acid, and compost. However, these valorisation processes generate effluents with high organic load and salinity, further stressing water resources. This study explores the potential of utilising these effluents to cultivate plant biomass in arid regions (sorghum or perennial pasture), which could serve as bioenergy, animal feed, or composting co-substrates, contributing to circular bioeconomy principles. The combined use of effluent as a water resource and the sowing of sorghum and pasture increased soil organic matter content and led to a slight reduction in pH (depth: 0.30–0.60 m) compared to the control treatment. The sorghum plots showed better establishment and higher dry biomass yield (32.6 Tn/ha) compared to the pasture plots (6.5 Tn/ha). Sorghum demonstrated better tolerance to saline soils and high salinity effluents, aligning with previous studies. Although pasture had a lower biomass yield, it was more efficient in nutrient uptake, concentrating more NPK, ash, and soluble salts. Sorghum’s higher yield compensated for its lower nutrient concentration. For biomass production, sorghum is preferable, but if nutrient capture from effluents is prioritised, summer polyphytic pastures are more suitable. These results suggest that the final selection between plant biomass alternatives highly depends on whether the goal is biomass generation or nutrient capture.